2015
DOI: 10.3389/feart.2015.00031
|View full text |Cite
|
Sign up to set email alerts
|

Striped domains of coarse-grained magnetite observed by X-ray photoemission electron microscopy as a source of the high remanence of granites in the Vredefort dome

Abstract: The characteristics of a coarse-grained high-remanence magnetite obtained from shocked Vredefort granite were investigated by X-ray magnetic circular dichroism (XMCD) analysis and X-ray absorption spectroscopy (XAS). The study utilized a spectroscopic photoelectron low-energy electron emission microscope (SPELEEM) and was conducted in the SPring-8 large-synchrotron radiation facility. It is generally believed that the strong and stable bulk remanence of Vredefort granites is due to the presence of minerals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A natural lodestone sample (Nichika Inc., Japan) mainly consists of the mineral magnetite. A loadstone sample also contains maghemite and hematite, which have been transformed from magnetite through natural weathering (oxidation) processes (Kubo et al, 2015; Wasilewski & Kletetschka, 1999). We use the loadstone data as a reference for a mixture of magnetite, maghemite, and hematite, even though the actual mixing ratios of the three FeO x species in the sample were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A natural lodestone sample (Nichika Inc., Japan) mainly consists of the mineral magnetite. A loadstone sample also contains maghemite and hematite, which have been transformed from magnetite through natural weathering (oxidation) processes (Kubo et al, 2015; Wasilewski & Kletetschka, 1999). We use the loadstone data as a reference for a mixture of magnetite, maghemite, and hematite, even though the actual mixing ratios of the three FeO x species in the sample were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Although the remanence of multi‐domain and pseudo single‐domain grains of unpinned or loosely pinned domain walls can be removed through the low‐temperature demagnetization, the remanence strongly pinned domain walls are excluded [ Özdemir and Dunlop , ]. The pinning may explain the remanence observed in multi‐domain and single‐domain‐like remanence in pseudo single‐domain grains [e.g., Kubo et al ., ]. Our estimated unblocking temperature of 145°C translates to an age of 14 kyr B.P.…”
Section: Resultsmentioning
confidence: 99%
“…Kubo et al. () used X‐ray magnetic circular dichroism analysis and X‐ray absorption spectroscopy to study the characteristics of coarse‐grained high‐remanence magnetite from the shocked Vredefort basement rocks. Based on their results the authors attributed the high remanent magnetism to postimpact hydrothermal activity but conceded that terrestrial lightning strikes could have intensified the remanence.…”
Section: Geomagnetism Of the Vredefort Impact Structurementioning
confidence: 99%
“…Salminen et al (2013) followed these results by conducting laboratory experiments on rock samples subjected to lightning strikes and concluded that lightning strikes could explain the observed high Q values. Kubo et al (2015) used X-ray magnetic circular dichroism analysis and X-ray absorption spectroscopy to study the characteristics of coarse-grained high-remanence magnetite from the shocked Vredefort basement rocks. Based on their results the authors attributed the high remanent magnetism to postimpact hydrothermal activity but conceded that terrestrial lightning strikes could have intensified the remanence.…”
Section: Magnetization Of the Archean Rocks In The Core Of The Structurementioning
confidence: 99%